2003
DOI: 10.1053/jhep.2003.50288
|View full text |Cite
|
Sign up to set email alerts
|

Week 48 Resistance Surveillance in Two Phase 3 Clinical Studies of Adefovir Dipivoxil for Chronic Hepatitis B

Abstract: H epatitis B virus (HBV) is a major cause of chronic liver disease with an estimated 400 million chronic carriers worldwide. Treatment of chronic hepatitis B aims to achieve sustained suppression of HBV replication, normalization in alanine aminotransferase levels, loss of serologic markers of hepatitis B e antigen or hepatitis B surface antigen, and improvement in liver histology. Before the recent regulatory approval of adefovir dipivoxil for the treatment of chronic hepatitis B in the United States, lamivud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 35 publications
1
83
1
2
Order By: Relevance
“…Our data are in agreement with previous studies that show ADV-resistant mutations are infrequent and delayed in treatment-naïve patients. 10,11,22 However, in contrast to previous reports in which no ADV-resistant mutations were detected in LAM-resistant patients after 1 year of ADV therapy, 23,24 our study indicated that the emergence of those mutations in LAM-resistant patients was frequently detected after 1 year of ADV therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data are in agreement with previous studies that show ADV-resistant mutations are infrequent and delayed in treatment-naïve patients. 10,11,22 However, in contrast to previous reports in which no ADV-resistant mutations were detected in LAM-resistant patients after 1 year of ADV therapy, 23,24 our study indicated that the emergence of those mutations in LAM-resistant patients was frequently detected after 1 year of ADV therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…In cases of HBV/HIV-1 coinfection, tenofovir and emtricitabine are also used. We studied whether the viruses have drug resistance mutations against these antiretroviral drugs with or without a history of antiretroviral treatments and confirmed the following resistance mutations: lamivudine/emtricitabine resistance mutations V173L, L180M, and M204I/V; adefovir resistance mutations A181V, I233V, and N236T; entecavir resistance mutations I169T, L180M, T184G, S202I, M204I/V, and M250V; and tenofovir resistance mutation A194T (1,2,24,32,34,35). Furthermore, major drug resistance mutations in HIV-1 were defined according to the criteria of the International AIDS Society (IAS)-USA and Stanford HIV drug resistance database (7,23).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the situation for lamivudine and famciclovir, the emergence of resistance to adefovir dipivoxil has been infrequent and delayed. No adefovir resistance mutations were identified in 467 chronic hepatitis B patients treated with adefovir dipivoxil for 48 weeks during phase III clinical studies or in a smaller cohort of 27 patients treated for up to 136 weeks (37,39 During enrollment of lamivudine-resistant patients into clinical trials of adefovir dipivoxil, we observed the rtV173L mutation in baseline viral sequences from many patients. Here we report a retrospective examination of lamivudine-resistant patients to determine the frequency of the rtV173L mutation and its association with mutations at positions rt180 and rt204.…”
mentioning
confidence: 76%